Comparative Anatomy and Histology of Digestive Organs of Fruit-Eating Bats (Pteropus Vampyrus Linnaeus, 1758) and Insect-Eating Bats (Rhinolopus pusillus Temminck, 1834) - Yani, Desi Arsita; Yuliyantika, Wanda Nurma (Proceeding International Conference on Science and Engineering, 2019)
Animal Bat consists of Megachiroptera and Microchiroptera. The difference between the two bats lies in the type and behavior of eating. Megachiroptera is a fruit-eating bat, while Microchiroptera is an insect-eating bat. This study aims to compare the digestive organ of fruit-eating bats (Pteropus vampyrus) and insect-eating bats (Rhinolopus pusillus). This research was conducted by observing macroanatomy and microanatomy in the digestive organ of both bats. Macroanatomy observation is done by looking at the shape and curvature of the analysis through organ photo media. Microanatomy observation was done by making organ preparations with hematoxylin-eosin staining and observed using a microscope. The digestive organ of fruit-eating bats and insectivores consists of the esophagus, stomach, duodenum and rectum. Macroanatomically, fruit-eating bats and insectivores differ in size, where the fruit-eating bat's digestive organs are larger than insectivorous bats. Microanatomically, fruit-eating bats and insectivores have relatively similar histological structures, which differ only in the size of the cell.